Funding of the Papal Army’s Campaign to Germany during the Schmalkaldic War (Theatrum historiae, 2017)
This article is based on the recently discovered text of accounting documentation led by the Papal secret accountant Pietro Giovanni Aleotti. He kept records of income and expenses of Papal chamber connected with the campaign of Papal army that was sent from Italy to Germany by Pope Paul III (Alessandro Farnese) in the frame of the first period of so called Smalkaldic War (1546–1547). The author publishes this unique source in extenso and completes the edition by the detailed analysis of the incomes and expenses of this documentation. The analysis is extended by three partial texts dealing with 1) so called Jewish tax that was announced by Paul III in the financial support of military campaign, 2) credit granting of this campaign by the bank house of Benvenuto Olivieri in connection with the collection of Papal tithe in the Romagna region and 3) staffing of the commanding officers of Papal army during this campaign (in the attachment one can find a reconstruction of the officers’ staff with identification of the most important commanders). In the conclusion the author tries to determine the real motives why Paul III decided to take part in this campaign. In comparison to the previous works the author accents mainly the efforts of the Farnese family to raise their prestige at the end of the pontificate of Paul III and their immediate financial interests that are reflected in the account documentation.
Keywords: Pope Paul III; Emperor Charles V; Schmalkaldic War; 1546–1547; Farnese family; accounts; edition; Pietro Giovanni Aleotti; Italy; Germany; military campaign